Determination of plasma levels of urea and creatinine in Pantanal horses Poconé region - MT - M. R. Guazina (Scientific Electronic Archives, 2016)
This study aimed to determine the plasma levels of urea and creatinine, besides evaluating the influence of sex and age factors on these substances in Pantaneiros horses, animals of high economic and social importance in the Pantanal. In Poconé-MT region, 80 animals were used, which were divided into four groups: Group 1: male foals (n= 20), aged 8 months and 2 years, Group 2: female foals (n= 20), aged 8 months and 2 years, Group 3: adult males (n= 20), aged from 3 years, Group 4: adult females (n= 20), aged from 3 years. All animals were classified as healthy after clinical examinations, as well as serum negativity for Equine Infectious Anemia (EIA). Blood samples for subsequent laboratory analysis were taken from the jugular vein. The mean values of urea and creatinine found for Pantaneiros horses were similar to other breeds of horses and did not vary influenced by the sexual factor, however plasma levels of creatinine increased with the age.